Frontiers Ahead. Issue 4 (November 2015) - Held, David; Nag, Eva‐Maria
Abstract : In its first five years Global Policy has become a unique hub generating research and cutting edge analysis. It has brought together world class academics and practitioners and is read by academics, experts and a wider general public.